Pengesanan masalah pendengaran oleh ibu bapa dan penggunaan alat bantu pendengaran sekumpulan pelajar cacat pendengaran = Identification of hearing impairment by parents, and hearing aid usage of a group of hearing-impaired children - Umat, Cila; O, Mazwin; Ismail, Noraidah; SZM, Maisarah (Penerbit Fakulti Sains Kesihatan Bersekutu, Universiti Kebangsaan Malaysia, 2000)
The aim of this study was to identify problems in recognizing hearing loss and its management among school children from Sekolah Rendah Pendidikan Khas, Kuantan. A total of 65 parents were chosen as subjects of this study. A set of questionnaire was distributed to the parents through the school teachers. Results showed mean age when hearing loss was suspected and the suspected condition confirmed was 22.5±16.7 and 37.8±33.4 months respectively. 45% of the parents suspected their child’s hearing loss when the latter was between 12 to 24 months old, and 37% of the diagnosis were confirmed by medical practitioners. Analysis on hearing aid usage showed almost half of the subjects (48%) were not fitted with hearing aids although diagnosis was made when the child was as young as 5 months old. These findings suggest that parents’ unawareness toward early identification of hearing problems let to late intervention.